2015
DOI: 10.1162/jocn_a_00785
|View full text |Cite
|
Sign up to set email alerts
|

The Default Mode of Human Brain Function Primes the Intentional Stance

Abstract: Abstract■ Humans readily adopt an intentional stance to other people, comprehending their behavior as guided by unobservable mental states such as belief, desire, and intention. We used fMRI in healthy adults to test the hypothesis that this stance is primed by the default mode of human brain function present when the mind is at rest. We report three findings that support this hypothesis. First, brain regions activated by actively adopting an intentional rather than nonintentional stance to a social stimulus w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
79
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 68 publications
8
79
0
1
Order By: Relevance
“…The DMN has since been shown to play a broader role in selfreferential thought, internally-generated thought, and social cognition (Amft et al, 2014;Mittner et al, 2016). The overlap in neural activation during self-reflection and ToM has inspired simulation theory, which holds that ToM is facilitated by imagining one's own reaction if put in a similar situation (Spunt et al, 2015). The ability to reconstruct past events (episodic memory) and imagine future ones (prospection), known as "mental time travel" (MTT; Tulving, 1983;Ingvar, 1985), is another cognitive faculty that is crucial for asking and providing explicit answers to the BQs.…”
Section: Event Cognition In Evolutionary Perspectivementioning
confidence: 99%
“…The DMN has since been shown to play a broader role in selfreferential thought, internally-generated thought, and social cognition (Amft et al, 2014;Mittner et al, 2016). The overlap in neural activation during self-reflection and ToM has inspired simulation theory, which holds that ToM is facilitated by imagining one's own reaction if put in a similar situation (Spunt et al, 2015). The ability to reconstruct past events (episodic memory) and imagine future ones (prospection), known as "mental time travel" (MTT; Tulving, 1983;Ingvar, 1985), is another cognitive faculty that is crucial for asking and providing explicit answers to the BQs.…”
Section: Event Cognition In Evolutionary Perspectivementioning
confidence: 99%
“…Does the LOA construct help integrate this diverse set of findings? Several proposals have attempted to integrate at least a subset of these findings, but these have primarily regarded the regions associated with increasing LOA in the present study, which we have recently demonstrated map well on to the dorsomedial PFC subsystem of the DMN (Spunt et al, 2015). For instance, Buckner and Carroll (2007) suggest that mental-state reasoning, perspective-taking, episodic memory, and prospection all depend on a process they call 'self-projection', which involves the mental simulation of events and experiences that transcend the immediate environment.…”
Section: Brain Regions For Conceptualizing An Action At Different Loasmentioning
confidence: 99%
“…The association of higher autistic‐like traits with lower dmPFC activation during spontaneous mentalizing has been reported in previous studies involving typical adults, such as during the uninstructed viewing of social scenes [Wagner et al, ], during no‐task periods (i.e., rest) in an instructed mentalizing task [Spunt et al, ], or while listening to live as compared to recorded speech [Rice and Redcay, ]. At the higher end of the autism spectrum, patients with ASD have repeatedly demonstrated reduced dmPFC activation during tasks related to spontaneous mentalizing, for instance, in response to animated shapes [Castelli et al, ; Kana et al, ; Kana et al, ], task‐irrelevant social content in naturalistic movie clips [Kana et al, ], or uninstructed exposure to face and voice stimuli [Wang et al, ].…”
Section: Discussionmentioning
confidence: 62%
“…Besides its significance for daily social functioning and its reliance on social brain regions including dmPFC and pSTS, spontaneous mentalizing has also been shown to be sensitive for individual differences in social abilities. For instance, the level of dmPFC activation during spontaneous mentalizing could be related to differences in autism‐related traits [Spunt et al, ; Wagner et al, ], real‐life social expertise [Powers et al, ], and the proneness to adopt the intentional stance [Kestemont et al, ; Moran et al, ]. Another line of research suggests that spontaneous mentalizing is particularly impaired in patients with autism spectrum disorders (ASD) [Abell et al, ; Senju et al, ; White et al, ].…”
Section: Introductionmentioning
confidence: 99%